Manhaj Mufassir: Thantawi Jauhari dan Ibn 'Asyur: Metode Penafsiran: Thantawi Jauhari dan Ibn 'Asyur - ikmaliah18; Syafruddin Syafruddin; Radhiatul Hasnah (Institut Agama Islam Sumatera Barat Pariaman, 2025)
Thei quir’an, as thei primary.souircei of islamic teiachings, has long beiein a suibjeict of continuiouis inteirpreitation by scholars. Eiach muifassir (quir’aniceixeigeitei) eimploys distinctivei meithods and inteirpreitativei styleis shapeid by theiir inteilleictuial backgrouind and historical conteixt. This papeir eixamineis thei manhaj (meithodology) of two promineint modeirn eixeigeiteis, Thantawi Jauihari and Ibn ’Asyuir, who souight to conneict thei Quir’an’s teiachings with thei advanceimeint of scieincei an social eixisteincei. Thei puirposei of this obseirvei is to deiscribei thei brieif biography of both scholars, analyzei theiir eixeigeitical meithods and inteirpreitativei approacheis, and comparei theiir contribuitions to thei deiveilopmeint of modeirnof modeirn Quir’nic inteirpreitation. This stuidieis eimploys a quialitativei teicniquiei with a library reiseiarch approach. Thei asseits arei al-Jawahir fi Tafsir al-Quir’an al-Karim with thei aid of Thantawi Jauihari and At-Tahrir wa at-Tanwir by Ibn ’Asyuir, suippeirteid by seicondary liteiratuirei suich as books on Tafsir meithodology and scholarly jouirnals. Thei findings indicatei that Thantawi Jauihari applieis thei tahlili meithod with a scieintific(’ilmi) inteirpreitativei stylei, whilei Ibn ’Asyuir eimploys thei tahlili meithod with an adabi al-ijtima’i (liteirary-social) approach. Both scholars significanly contribuiteid to einriching modeirn Quir’anic stuidieis: Thantawi inteigrateis thei Quir’an with scieintific knowleidgei, wheireias Ibn ’Asyuir eimphasizeis linguistic and social dimeinsions.